Irigaray and Deleuze : Experiments in Visceral Philosophy - Lorraine, Tamsin (Cornell University Press, 2018)
For Tamsin Lorraine, the works of Luce Irigaray and Gilles Deleuze open up new ways of thinking about subjectivity. Focusing on the affinities between the theorists' views-while addressing weaknesses of each-she offers both a cogent analysis of their often challenging writings on this topic and an accessible introduction to their philosophical projects. Through her readings she articulates an approach to subjectivity as an embodied, dynamic process, one that speaks to beliefs about personal identity as well as to the practical problems people face in their relations with one another.Lorraine begins by distinguishing between "conceptual" and "corporeal" considerations of subjectivity and by reviewing recent interdisciplinary efforts to theorize the body. She then turns to Irigaray and Deleuze, finding in the former's notion of the "feminine other" and in the latter's, unique conceptions of nomadic thinking inspiration for a model designed to overcome mind/body dualisms. Her analysis of Irigaray and Deleuze suggests a conception of humanity which amounts to a visceral philosophy-a way of thinking that is receptive to the fluxes of dynamic life forces.